Spatial Diffusion of Local Economic Shocks in Social Networks: Evidence from the US Fracking Boom - Diemer, Andreas (Journal of Labor Economics, 2026)
I study the role of social networks in the propagation of economic shocks across space. Combining comprehensive data on US online friendships with extraction activity during the fracking boom, I show that exogenous changes in economic conditions in one area affect outcomes in socially proximate places, regardless of how far apart they are geographically. Social exposure to fracking generates a wage spillover amounting to one-third of every dollar of energy produced in a county’s social network. This spillover decays slowly in space and is associated with a large mobility response. Diffusion mainly stems from the commuting of transient fracking workers.